Engaged Buddhism & Women in Black: Our Grief Is Not a Cry for War - Candace Walworth (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
This paper explores principles, practices, and manifestations of engaged Busshism in the United States. It includes a personal narrative based on the author's participation in Women in Black (a silent, symbolic protest against war) and classroom stories based on the author's experience teaching at a Buddhist-inspired university.